Severe congenital neutropenia: pathophysiology of leukemogenic transformation - J. Skokowa; K. Welte (Онкогематология, 2022)
Severe congenital neutropenia (CN) is a heterogeneous disorder of hematopoiesis characterized by a maturation arrest of granulopoiesis at the level of promyelocytes with peripheral blood absolute neutrophil counts (ANC) below <0,5×10 9/L. In this review we summarize our current knowledge on pathophysiolgy of AML in CN patients.There are two major subtypes of CN as judged by inheritance, 1) autosomal dominant trait defined by ELA2 mutations consisting 60% of patients and 2) autosomal recessive trait comprising approximately 30% of patients. CN is considered as a pre-leukemic syndrome, since after ten years of observation the cumulative incidence of acute leukemia is 21%. Acquired G-CSFR mutations are detected in approx. 80% of CN patients who developed AML. CN patients with acquired G-CSFR mutations define a group with high risk for development of leukemia.